Riding the Rails: Black Railroad Workers in Canada and the United States - Carson, Jenny (Labour / Le Travail, 2002)
The article reviews the books, "My Name’s Not George: The Story of the Brotherhood of Sleeping Car Porters in Canada," by Stanley G. Grizzle, "Brotherhoods of Color: Black Railroad Workers and the Struggle for Equality," by Eric Arnesen, and "Pullman Porters and the Rise of Protest Politics in Black America, 1925-1945," by Beth Tompkins Bates.